Patient priorities in relation to surgery for gastric cancer: qualitative interviews with gastric cancer surgery patients to inform the development of a core outcome set. Issue 2 (12th February 2020) - Alkhaffaf, Bilal; Blazeby, Jane M; Bruce, Iain A; Morris, Rebecca L
Abstract : Objective: The reporting of outcomes in surgical trials for gastric cancer is inconsistent. The GASTROS study (GA stric Cancer S urgery TR ials R eported O utcome S tandardisation) aims to address this by developing a core outcome set (COS) for use in all future trials within this field. A COS should reflect the views of all stakeholders, including patients. We undertook a series of interviews to identify outcomes important to patients which would be considered for inclusion in a COS. Setting: All interviews took place within the UK. Interviews were carried out face-to-face at hospitals and cancer support centres or via the telephone. Participants: Twenty participants at varying stages of recovery following surgery for gastric cancer with curative intent. Design: Qualitative design using semistructured interviews, supported by an interview guide which was iteratively modified; thematic analysis was used to explore patient priorities. Results: Six themes enveloping 38 outcomes were identified; surviving and controlling cancer, technical aspects of surgery, adverse events from surgery, recovering from surgery, long-term problems following surgery and long-term life impact of surgery. The 'most important' patient priority was to be 'cured of cancer'. Conclusion: Surgical trials for gastric cancer should consider broader priorities of patients when choosing which outcomes to report. This study highlighted the importance of longer-term outcomes such as cancer survival. Outcomes identified in this study will be used to inform an international Delphi survey to develop a COS in this field.